Kleptoparasitism in Arcotheres exiguus (Burger, 1895): Symbiotic Dynamics and Reproductive Implications in Paphia malabarica from the Southwest Coast of India - Suryapraba, V.; Angmo, Sonam; Ashpel, Mano M. R.; Nikhil, Kottapalli; Iburahim, Abuthagir; Mandal, Sangeeta; Porayil, Layana; Nayak, Binaya Bhushan (International Journal of Bio-resource and Stress Management, 2025)
The present study conducted from April to September, 2024 along the southwest coast of Maharashtra, India, to investigate the host–symbiont relationship between the pinnotherid pea crab Arcotheres exiguus and its bivalve host Paphia malabarica. Integrated morphological and molecular techniques, including mitochondrial COI gene amplification, were employed to confirm the crab species. Morphological identification and morphometric measurements were performed using a stereo zoom microscope. Among 320 clams examined, 41.56% were found infested, with a predominance of ovigerous females, indicating a strong reproductive dependence on the host. Morphological analysis revealed distinct sexual dimorphism: males exhibited smaller, calcified carapaces, while females possessed broader, flexible carapaces and pleopods carrying between 611 and 3,750 eggs. The crabs occupied the mantle cavity of the bivalves, displaying kleptoparasitic tendencies by relying on host-filtered food, potentially compromising host health and immune function. Notably, no clam was observed to house both sexes simultaneously, suggesting that mating likely occurred externally. While A. exiguus benefited from shelter and reproductive conditions, the direct benefits to P. malabarica remain unclear. This study highlights the ecological role of P. malabarica as a critical reproductive habitat for A. exiguus and emphasizes the importance of conserving host bivalve populations. These findings contribute baseline knowledge on marine kleptoparasitism and underline the need for further research to evaluate the long-term ecological impacts of pinnotherid crabs on their bivalve hosts.